Further Extension of Consultation Cycles Due To Covid-19 Pandemic, and Suspension of Framework To Address Excessive Delays in Article IV Consultations and Mandatory Financial Stability Assessments. (Policy Papers; Policy Paper ;, 2020)
Notwithstanding the ongoing intensive policy dialogue with the membership during the COVID-19 pandemic, there is growing need for resuming Article IV consultations and mandatory Financial Stability Assessments (FSAs). However, the resumption of Article IV consultations over the coming months will need to be gradual, remain focused on the crisis and related challenges, and be undertaken flexibly. Staff recommends a further extension of consultation cycles to accommodate the gradual nature of the restart. Staff also recommends that the application of the framework to address excessive delays in the completion of Article IV consultations and mandatory FSAs be temporarily suspended.